2019
DOI: 10.3390/met9111207
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Creep Properties Improvement of Ti-6Al-4V Alloy Specimens Produced by Electron Beam Powder Bed Fusion Additive Manufacturing

Abstract: Thanks to their excellent mechanical strength in combination with low density, high melting point, and good resistance to corrosion, titanium alloys are very useful in many industrial and biomedical fields. The new additive manufacturing methods, such as Electron Beam Powder Bed Fusion based on the deposition of metal powders layers progressively molten by electron beam scanning, can overcome many of the machining problems concerning the production of peculiar shapes made of Ti alloys. However, the processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…While Al tends to enter the α phase, the V tends to enter the β phase [24]. In the images taken for the 8 specimens at the same magnification, the dark regions show the α phase, while the light regions present the β phase [25]. The presence of delamination wear, abrasion and debris in the SEM pictures of Ti-6Al-4V is in accordance with the test results of other titanium alloy testing [26].…”
Section: E Scanning Electron Microscopy (Sem)supporting
confidence: 77%
“…While Al tends to enter the α phase, the V tends to enter the β phase [24]. In the images taken for the 8 specimens at the same magnification, the dark regions show the α phase, while the light regions present the β phase [25]. The presence of delamination wear, abrasion and debris in the SEM pictures of Ti-6Al-4V is in accordance with the test results of other titanium alloy testing [26].…”
Section: E Scanning Electron Microscopy (Sem)supporting
confidence: 77%
“…Other studies have assessed the machinability of EBM-fabricated samples in assisted surface finishing treatments using different cooling techniques [ 133 ], [ 134 ]. The internal porosity defect can be reduced by subjecting samples to subsequent treatments such as hot isostatic pressing and other heat processes [ 135 ]. Another important aspect are the scanning strategies employed during the EBM process [ 136 ], as they could play a role in minimizing internal porosity, a characteristic that reduces fatigue strength.…”
Section: Structure and Microstructure Of Ti6al4v Alloy Prototypes Obtained Via Electron Beam Meltingmentioning
confidence: 99%
“…Their mechanical performance, for instance, has been assessed by means of Creep tests. Aliprandi et al [ 135 ], [ 160 ] investigated the mechanical behavior of EBM-fabricated parts at temperatures between 400 and 600 °C. They reported that a better tensile performance at these temperatures is driven by a subsequent surface smoothing and observed in samples whose microstructure (basket weave) is aligned to the loading direction and has elongated grains along the tensile direction.…”
Section: Properties Of Ebm-manufactured Ti–6al–4v Implantsmentioning
confidence: 99%
“…Furthermore, defects can be caused by lack of fusion, unmelted or partially melted powder and gas entrapment occurring during the LPBF build process (Eliaz et al, 2020). These issues can impact the surface roughness of an LPBF part which in turn can influence properties (Aliprandi et al, 2019).…”
Section: Build Parameter Studiesmentioning
confidence: 99%